Learning from reflective journaling; the experience of navigators in assisting patients access to health and social resources in the community. Issue 6 (2nd November 2022) - Gauthier, Alain P.; Bourgoin, Nathalie; Ndihokubwayo, Natacha; Lemonde, Manon; Toal-Sullivan, Darene; Timony, Patrick E.; Warnet, Carolynn; Chomienne, Marie-Hélène; Kendall, Claire E.; Premji, Kamila; Dahrouge, Simone
ABSTRACT: We developed and implemented a person-centered navigation model integrated in primary care where patients were referred to the Access to Resources in the Community (ARC) study by their primary care provider (PCP). The purpose of this paper is to explore the lay navigators' learning experience as reflected in their journals and present implications for education and health promotion practice. Sixty-six journal entries from two navigators were analysed. To code the data, we used a newly developed framework based upon the theory-informed lay navigator training programme. Five unique themes were identified: 1) Gaining and Building Trust, 2) Developing Empathy, 3) Experiencing Hope and Optimism, 4) Feeling Helplessness and 5) Celebrating Gains and Successes . The five themes identified paint a sequential picture of the journey of leading individuals from primary care to health and social community resources. This innovative approach has expanded our understanding of how navigators learn in practice, more specifically how they learn from patients and how they develop knowledge and skills in person-centered care. Incorporating reflective journaling as a regular practice provides situational awareness and leads to enhanced learning. Practising person-centered care also develops when a trusting and empathetic relationship is established.